Definição taxonômica, variação acústica de Adenomera marmorata Steindachner, 1867 (Anura: Leptodactylidae) e diversidade críptica nas espécies de Mata Atlântica do gênero Adenomera a partir de evidências moleculares - Pedro Paulo Goulart Taucce (2013)
The genus Adenomera comprises 15 species distributed through South America, except in the Patagonian Region. Within them, A. marmorata is a problematic species since its type locality is uncertain. The advertisement call of three A. marmorata populations is described based on specimens collected at six localities of the states of Rio de Janeiro and São Paulo, including the putative type locality of the species. As well as most Adenomera species, the advertisement call of A. marmorata consists in one short and unpulsed note emitted several times per minute with harmonical structure. The three groups analyzed in this study differed mainly in the call duration parameter, which is positively correlated with temperature. Bioacoustics, literature and field data were used to define A. marmorata and to make conclusions about its putative type locality. We concluded that A. marmorata corresponds to the most abundant species of Adenomera present in the municipality of Rio de Janeiro, which is the probable type locality of the species, and is distributed throughout the states of Rio de Janeiro and São Paulo. We agreed with previous studies, concluding that Leptodatylus trivitattus is a junior synonym of A. marmorata and Leptodactylus nanus is a valid species.